Clinical Outcomes of Repair of Complete Detachment of Medial Collateral Ligament at the Tibial Insertion in Bilateral Total Knee Arthroplasty. (21st July 2022) - Jin, Cheng; Song, Eun-Kyoo; Jin, Quan-He; Seon, Jong-Keun; Sun, Si-Mei
Abstract : Purpose . Complete detachment of the medial collateral ligament (MCL) may occur during medial release of total knee arthroplasty (TKA) in patients with severe varus knee osteoarthritis. This study was to determine functional and stability outcomes of repaired knee with complete detachment of MCL compared to those of contralateral nondetached MCL in patients with bilateral TKA. Methods . Records of 1052 consecutive knees undergoing bilateral TKA from 2003 to 2015 were retrospectively reviewed. Of which, 45 patients were repaired for complete MCL detachment injury (2.1%) at tibial insertion in one side (repaired group). MCL was not detached in the contralateral side (control group). Clinical evaluation was performed preoperatively and at the final follow-up using KS and WOMAC scores between two groups. Similarly, stability was compared on a valgus stress radiograph between two groups. Results . Two patients had insufficient data. Hence, 43 patients were included after a minimum of 5 years follow-up. There were no significant differences in terms of alignment and clinical outcomes between the two groups either preoperatively or at the final follow-up (p > 0.05 ). Radiographic stability also showed no differences between repaired and control groups in extension and 30° of flexion (p = 0.208 and p = 0.125 ). Conclusions . For tibial detachment of the MCL during TKA, repair with suture anchor provided good clinical and stability results, similar to TKA without MCL injury. Therefore, repair with a suture anchor is a reliable method that provides good clinical and stability outcomes in patients with MCL injury during TKA.